Some considerations regarding the port handling contract - Díaz de la Rosa, Angélica (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
Port handling activities involve a set of operations that are primarily technical and material in nature, carried out before and after the transfer of goods, and conducted within the port area. These operations are essential for the effective performance of cargo transportation. Although there is an operational continuity between the activities inherent to carriage and those related to the handling of goods, from a legal standpoint, such operations may be performed either under a self-provision regime, or within the framework of the carriage of goods contract itself, or -finally- through an independent contract for the handling of goods. The LNM -Marine Navigation Act- establishes a specific liability regime for port handlers, which does not preclude them —when applicable— from benefiting from other liability regimes provided by the same legal framework.